1982
DOI: 10.1161/01.hyp.4.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Acute responses to arterial pressure and plasma renin activity to converting enzyme inhibition (SQ 20,881) in serially studied dogs with neonatally-induced coarctation hypertension.

Abstract: propriately "normal" (i.e., nonsuppressed) plasma renin activity (PRA) and normal renal function. 1 The abnormal renin/volume relationship in coarcted dogs is demonstrable at normal, low, and high steady-state sodium intakes.3 These observations are compatible with the hypothesis that coarctation hypertension is a renin-mediated process, initiated by balanced underperfusion of total renal mass via transient reninangiotensin excess, the latter generating volume expansion sufficient to normalize renal perfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Group 1 dogs were also included in 0-to 1-year studies reported previously. 16 " 18 Group 2 dogs, born in late 1978, contained three coarcted and three littermate control dogs drawn from two litters; Group 2 studies reported here were carried out in 1980. The technique of neonatal aortic banding and the littermate-control experimental design have been previously described.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Group 1 dogs were also included in 0-to 1-year studies reported previously. 16 " 18 Group 2 dogs, born in late 1978, contained three coarcted and three littermate control dogs drawn from two litters; Group 2 studies reported here were carried out in 1980. The technique of neonatal aortic banding and the littermate-control experimental design have been previously described.…”
Section: Experimental Animalsmentioning
confidence: 99%